Family influence in the choice of undergraduate medical students at UEPA - Campus VIII – Marabá (Research, Society and Development, 2021)
Introduction: The importance of professional choice involves symbolic and material meanings, having reflections throughout all or a good part of an individual's life. Thus, recognizing the breadth of the motivational factors of this choice, this study seeks to highlight and untangle the influence of the family environment in medical students, taking samples from students from the Universidade do Estado do Pará (UEPA) - Marabá. Objective: To understand the presence or absence of family influence in the choice of the medical course of students at UEPA Marabá, its influential aspects and levels of occurrence. Methodology: This is an observational, analytical cross-sectional study, using a survey questionnaire to identify and evaluate the family factors involved in the professional choice of the medical student residing in Marabá, with subsequent assembly of tables and graphs to analyze the results of the research. Results: It was found through the verification of data from the questionnaire applied to 105 students that there is a decisive family influence in a significant portion of the students, although the relative majority reported the opposite. Conclusion: We conclude that there is a family influence on medical students at the University of the State of Pará and that this is multifactorial, with some aspects standing out in relation to others, however, there is a need for further studies on the subject in order to deepen understanding about.